Dakṣayāgaṃ : āṭṭakkatha - Rāmakrṣṇapiḷḷa, Ji., 1890-1959 (Sāhityapṟavarttaka Sahakaraṇasaṅkhaṃ : [Sales Dept.], Nāṣanal Bukksṯṯāḷ, 1972)
Commentary, with text, on Dakṣayāgaṃ, a libretto for Kathakali, dance drama of Kerala, by Irayimmantampi, 1783-1856, Malayalam literatteur.